Menggali Kreativitas, Kompetensi, Konsep Manusia Dan Ilmu Pengetahuan Dalam Perspektif Al-Qur’an - Muhammad Efendi; Isnaini (Mataram University, 2025)
This article discusses and examines the Qur'anic verses on creativity, competence, human concepts, and science in the perspective of the Qur'an in an effort to build an integrative understanding of human character and abilities. This research uses the library research method by analyzing the verses of the Qur'an and the opinions of mufasir and scholars related to human nature, the potential of reason, creativity, and the concept of science. The results of the study show that the Qur'an views humans as beings with great potential (potentialist people), who are endowed with intellect, heart, intuition, and creative ability to manage life. Creativity and competence are considered part of the caliphate's mandate, while science is the main foundation for the perfection of human duties as servants and caliphs on earth. This research emphasizes that creativity and competence in Islam are inseparable from the value of monotheism and the orientation of benefits. Other findings show that the concept of man in the Qur'an is not only oriented towards external potential, but also emphasizes the importance of self-awareness, faith, and the ability to understand God's signs in the universe. Meanwhile, science is understood as a gift as well as a mandate that must be developed through observation, reflection, and deep meaning methods of reality. In conclusion, the Qur'an provides a philosophical and practical foundation for the development of human creativity and competence, and offers a scientific paradigm that is integrative, humanistic, and oriented towards divine values. This article is expected to be an academic contribution in strengthening the paradigm of Islamic education that is relevant to the needs of the times.